Effect of Cryopreserved Culture of Pancreas Microfragments on Immune Status of Rats with Aloxane Diabetes Development - Ostankova, L. V.; Pobelensky, O. N.; Ostankov, M. V.; Goltsev, A. N. (Problems of Cryobiology and Cryomedicine, 2006)
The effect of cryopreserved culture of newborn piglet pancreas microfragments on rat’s immune status in the model of aloxane diabetes (AD), similar to human insulin-dependent diabetes mellitus has been studied. Administration of pancreas microfragment cryopreserved culture was demonstrated as contributing to cell and humoral immunity link recovery. The most manifested effect was after its introduction into parapancreatic fat.